(untitled) (Nepalese Journal of Radiology, 2012)
Hydatid disease (echinococcosis) commonly involves liver while other known extrahepatic sites of involvement are lung, heart, brain, kidney, bones, spleen, pancreas, adrenal and muscles.1-3 Ultrasonography (US) and computed tomography (CT) features are characteristic especially in hepatic disease and hence diagnosed easily, while isolated extrahepatic diseases are sometimes difficult to diagnose. Here, we present an interesting case of hydatid cyst in paraspinal muscle with unusual clinical and imaging features, but treated successfully inspite, initial diagnostic dilemma. Imaging features and follow up result are discussed. NJR I VOL 2 I ISSUE 1 31-34 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6977